Penelitian Peranan Program Pelatihan Konselor Bisnis dalam Peningkatan Kemampuan Peserta Pelatihan Berbasis Evaluasi Diri (Studi Kasus Program Pelatihan APEC-IBIZ Indonesia) - - Farida; Rizal Syarief; Illah Sailah (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2011)
The role of SME’s in domestic economics increasing progressively. Especially after crisis 1997, in the year 1997 all leaders of Asia Pacific Economic Cooperation (APEC) country has gives recommendation to APEC organization. As a following step in the year 2001 has been established so-called APEC-IBIZ (International Network of Institutes of Small Business Counsellor) who has been appointed as a training programe for a Business Counsellor and eligible in giving certificate for all countries participants. The objectives of this study are: (1) to know the descriptive of the participant of training; (2) to analys the trainers from the aspects of training through the comments of training participant; (3) to evaluate improvement ability of participant of training base on its self evaluation. The survey has been carried out with by using Statistical Package for Social Science (SPSS) model 12. The population of this study are determinate by using all of the training program (88) and the sample are 30 respondents. Analysis of the trainners  and the training aspect toward with coming from the opinion of the programme participant is consider as excellent due to the majority of the participant chose between scale 5 and 4. And the third finding according to the objectives of this study indicate that the ability of the participant has been increased of the training programme.